OCT layered tomography of the cornea provides new insights on remodeling after photorefractive keratectomy. Issue 2 (31st July 2017) - Chandapura, Rachana S.; Shetty, Rohit; Shroff, Rushad; Shilpy, Neha; Francis, Mathew; Sinha Roy, Abhijit
Abstract : OCT (optical coherence tomography) of corneal layers was generated to analyze the remodeling of the epithelium and stroma after photorefractive keratectomy (PRK). Myopic PRK was performed in 15 patients. One eye underwent manual scraping of epithelium while the other was treated with Epi clear. Epi clear allowed a gentler removal of the epithelium compared to manual scraping. Scheimpflug (Pentacam, OCULUS Optikgerate Gmbh, Wetzlar, Germany) and OCT (RTVue, Optovue Inc., Fremont, California, USA) scans of the cornea were performed before and after PRK (3 months). The OCT scanner and Pentacam acquired 8 and 25 radial 2‐D scans of the cornea, respectively. The results showed similar topographic changes on the anterior corneal surface between Scheimpflug and OCT imaging. The curvature of the underlying anterior surface of the stroma after PRK was similar to the anterior corneal surface (air‐epithelium interface), when measured with OCT. Aberrometric changes were mostly similar between Scheimpflug and OCT. However, Scheimpflug imaging reported greater changes in spherical aberration and corneal higher order aberrations than OCT after PRK. This is the first study to quantify the curvatures of the stromal layers with OCT after PRK. New insights were gained, which could be useful for refinement of surgical ablation algorithms, refractive procedures and detection of ectasia. Abstract : The study presents a novel mapping of curvature of the Bowman's layer (BL) in human eyes undergoing photorefractive keratectomy (PRK) using optical coherence tomography (OCT). This allowed precise validation of the accuracy of the delivered therapy. While clinical Scheimpflug imaging reported a significant increase in corneal spherical aberration (SA), layered tomography with OCT reported minimal induction in SA after PRK. BL curvature mapping can have important implications in refractive surgery and intraocular lens planning.